A Review of Culture-Based Learning at Primary Level In Indonesia - Yuyun Elizabeth Patras; Ai Juliani; Nina Nurhasanah; Arifin Maksum; Rais Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to present a review of culture-based learning in primary school. The results of research have been found in several articles related to the implementation of culturally responsive teaching (CRT) or culture based learning. The findings in these articles were then used as a basis for formulating a new way of discussing culture-based learning (CRT) at the primary school level. The methodology used in this study is a literature search of articles in both Indonesian and English in 2018-2021 sourced from Google Scholar, Scopus.com, and Garuda search sites using the keywords “implementation of culturally responsive teaching”, “implementation of culture-based learning".  The data analysis procedure was performed based on a qualitative approach. The research results show that culture-based learning or CRT can be implemented in learning resources as an inculcation of ethical, moral and character values of students. The new way that can be done is to implement culture-based learning at the primary school level, which requires commitment from all elements of education and school members to create learning according to students' needs by involving cultural elements.